Manganese-Based Targeted Nanoparticles for Postoperative Gastric Cancer Monitoring via Magnetic Resonance Imaging - Li, Ke; Li, Peng; Wang, Yang; Han, Shuang (Frontiers in Oncology, 2020)
Postoperative recurrence is a common and severe problem in the treatment of gastric cancer; consequently, a prolonged course of chemotherapy treatment is inevitable. Monitoring by imaging could provide an accurate evaluation of the therapeutic effects, which would be beneficial to guide a treatment strategy adjustment over time. However, current imaging technologies remain insufficient for the continuous postoperative monitoring of gastric cancer. In this case, molecular imaging offers an efficient strategy. Targetable contrast agents are an essential part of molecular imaging, which could greatly enhance the accuracy and quality of monitoring. Herein, we synthesized a Mn-based contrast agent for magnetic resonance imaging (MRI) of gastric cancer monitoring. Initially, small-sized Mn3O4 nanoparticles (NPs) were synthesized. Then, a functionalized polyethylene glycol (PEG) lipid was attached to the surface of the Mn3O4 NPs, to improve biocompatibility. The targetable MRI contrast agent (Mn3O4@PEG-RGD NPs) was further prepared by the conjugation of the arginine-glycine-aspartic acid (RGD) peptides. The completed Mn3O4@PEG-RGD NPs had the small size of 7.3±2.7 nm and exhibited superior colloidal stability in different solution environments. In addition, Mn3O4@PEG-RGD NPs exhibited reliable biotolerance and low toxicity both in vitro and in vivo. Imaging experiments amply demonstrated that Mn3O4@PEG-RGD NPs could efficiently accumulate in gastric cancer tissues and cells via RGD mediation, and immediately significantly increased the MRI effects. Through this study, we can conclude that Mn3O4@PEG-RGD NPs have the potential to be a novel MRI contrast agent for the postoperative monitoring of gastric cancer.